Análisis del comportamiento de la demanda y de la planificación del lado aire en infraestructura aérea: una aproximación al caso global (2021)
The planning and provision of airports requires a very detailed analysis because they are infrastructures that are very expensive, require extensive land use and are long-term. Part of this planning requires estimating future demands and establishing certain operational characteristics of the airport. Due to wind reasons, it may happen that the air side of the aerodrome has several runways, in different orientations. This study seeks to explore what factors explain the demand of an airport and study the levels of demand with the air side supply. Multivariate linear regression models were performed to estimate the demand for passengers (model 1), cargo (model 2) and air operations (model 3) of 85 airports in the world. For model 1, it was found that the variables that help to predict the total passenger demand per year at an airport are the location of the airport in a capital city or city considered tourist, the operation of the airport as an operations hub, the population of the associated city, the average change in population, GDP, and the maximum annual capacity of the airport runway set. For cargo, they are the location of the airport in a capital city or city considered tourist, the operation of the airport as an operations hub, the average change in population and GDP per capita. For air operations they are the operation of the airport as an operations hub, the population of the associated city, GDP, and the total number of runways that the airport has. Due to the global nature of the sample used, the results can be used as support in decision-making for the planning of future airports or the expansion of existing ones in the world.